2017
DOI: 10.1364/boe.8.004629
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and combination of rotational imaging optical coherence tomography and selective plane illumination microscopy for embryonic study

Abstract: Several optical imaging techniques have been applied for high-resolution embryonic imaging using different contrast mechanisms, each with their own benefits and limitations. In this study, we imaged the same E9.5 mouse embryo with rotational imaging optical coherence tomography (RI-OCT) and selective plane illumination microscopy (SPIM). RI-OCT overcomes optical penetration limits of traditional OCT imaging that prohibit full-body imaging of mouse embryos at later stages by imaging the samples from multiple an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…The study included corneal SHG imaging of diseases and healthy state as well as collagen microstructural response to changes in intraocular pressure correlating the results also with OCT. Multimodal microscopy demonstrated improved molecular and multi-scale structural contrast also for ex-vivo and in-vivo skin imaging [174,175]. A recent study demonstrated the combination of tomographic OCT with selective plane illumination microscopy (SPIM) for the study of mouse embryon development employing fluorescence microscopy with the potential to be also combined with MPM [176]. MPM has been shown to provide important metabolic information in addition to cellular structural details in various skin disorders and diseases such as basal cell carcinoma and other skin cancers, hemangioma, psoriasis, pigmented lesions, or connective tissue diseases [177,178].…”
Section: Oct and Non-linear Optical Microscopy (Nlom)mentioning
confidence: 99%
“…The study included corneal SHG imaging of diseases and healthy state as well as collagen microstructural response to changes in intraocular pressure correlating the results also with OCT. Multimodal microscopy demonstrated improved molecular and multi-scale structural contrast also for ex-vivo and in-vivo skin imaging [174,175]. A recent study demonstrated the combination of tomographic OCT with selective plane illumination microscopy (SPIM) for the study of mouse embryon development employing fluorescence microscopy with the potential to be also combined with MPM [176]. MPM has been shown to provide important metabolic information in addition to cellular structural details in various skin disorders and diseases such as basal cell carcinoma and other skin cancers, hemangioma, psoriasis, pigmented lesions, or connective tissue diseases [177,178].…”
Section: Oct and Non-linear Optical Microscopy (Nlom)mentioning
confidence: 99%
“…With the further improvement in the imaging speed of Brillouin microscopy [ 105 ] as well as the integration of the two systems [ 106 ], OCT-guided direct biomechanical assessment in the beating mouse embryonic heart is potentially possible. In another multimodality configuration, the lack of molecular contrast from OCT was complemented by light-sheet microscopy as well as the establishment of rotation-based OCT imaging [ 107 , 108 ]. In addition to imaging, a number of manipulation methods have been established for mouse embryos, such as controlled microinjection to the blood circulation [ 109 , 110 ] and cardiac optogenetic pacing [ 111 ], which set a platform for mechanistic studies investigating the interplay between molecular and biomechanical factors in mammalian cardiogenesis.…”
Section: Perspective On Future Developmentsmentioning
confidence: 99%
“…In this feature issue of Biomedical Optics Express, we have collected several papers [3][4][5] that represent some of the technologies discussed at the NTM symposium that moved the field, both in terms of the technology and also the biological applications.…”
Section: Novel Techniques In Microscopy (Ntm)mentioning
confidence: 99%